Extracts of the tiger milk mushroom (Lignosus rhinocerus) enhance stress resistance and extend lifespan in Caenorhabditis elegans via the DAF-16/FoxO signaling pathway - Kittimongkolsuk, Parinee; Roxo, Mariana; Li, Hanmei; Chuchawankul, Siriporn; Wink, Michael; Tencomnao, Tewin (Pharmaceuticals, 2021)
The tiger milk mushroom, Lignosus rhinocerus (LR), exhibits antioxidant properties, as shown in a few in vitro experiments. The aim of this research was to study whether three LR extracts exhibit antioxidant activities in Caenorhabditis elegans. In wild-type N2 nematodes, we determined the survival rate under oxidative stress caused by increased intracellular ROS concentrations. Transgenic strains, including TJ356, TJ375, CF1553, CL2166, and LD1, were used to detect the expression of DAF-16, HSP-16.2, SOD-3, GST-4, and SKN-1, respectively. Lifespan, lipofuscin, and pharyngeal pumping rates were assessed. Three LR extracts (ethanol, and cold and hot water) protected the worms from oxidative stress and decreased intracellular ROS. The extracts exhibited antioxidant properties through the DAF-16/FOXO pathway, leading to SOD-3 and HSP-16.2 modification. However, the expression of SKN-1 and GST-4 was not changed. All the extracts extended the lifespan. They also reduced lipofuscin (a marker for aging) and influenced the pharyngeal pumping rate (another marker for aging). The extracts did not cause dietary restriction. This novel study provides evidence of the functional antioxidant and anti-aging properties of LR. Further studies must confirm that they are suitable for use as antioxidant supplements.